Human reproductive system disturbances and pesticide exposure in Brazil Distúrbios do sistema reprodutivo humano e exposição a pesticidas no Brasil - Sergio Koifman; Rosalina Jorge Koifman; Armando Meyer (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
The observation of reproductive disturbances in humans and in the wildlife has been reported in the last decade in different countries. Exposure to different chemicals possibly acting in the endocrine system or endocrine disruptors, including pesticides, has been a hypothesis raised to explain the observed changes. This paper aimed to present results of an epidemiological ecologic study carried out to explore population data on pesticides exposure in selected Brazilian states in the eighties and human reproductive outcomes in the nineties. Pearson correlation coefficients were ascertained between available data pesticides sales in eleven states in Brazil in 1985 and selected further reproductive outcomes or their surrogates. Moderate to high correlations were observed to infertility, testis, breast, prostate and ovarian cancer mortality. Despite the restrains of ecologic studies to establish cause-effect relationships, the observed results are in agreement with evidence supporting a possible association between pesticides exposure and the analyzed reproductive outcomes. A observação de distúrbios reprodutivos em seres humanos e na vida animal tem sido relatada em diferentes países na última década, sendo apontada como possível explicação para tal fenômeno, a exposição a diversas substâncias químicas com possível interferência no sistema endócrino, incluindo pesticidas. Este trabalho apresenta os resultados de um estudo epidemiológico, com delineamento ecológico explorando dados de exposição a pesticidas durante os anos oitenta, em estados brasileiros selecionados e distúrbios reprodutivos observados nos anos noventa. Foram obtidos coeficientes de correlação de Pearson entre o volume de vendas de pesticidas em onze estados brasileiros em 1985 e indicadores diretos ou substitutos da ocorrência de distúrbios reprodutivos nas mesmas localidades. Coeficientes de correlação moderados e elevados foram observados para a maioria dos indicadores dos desfechos analisados; infertilidade e câncer do testículo, mama, próstata e ovário. Apesar das limitações inerentes aos estudos ecológicos quanto ao estabelecimento de relações de causa-efeito, os resultados observados estão em concordância com as evidências, apoiando uma possível associação entre a exposição a pesticidas e os distúrbios reprodutivos analisados.